DESIGN AND DEVELOPMENT OF ENZALUTAMIDE-ENCAPSULATED POLYCAPROLACTONE NANOPARTICLES FOR PROSTATE CANCER: A BOX–BEHNKEN STATISTICAL APPROACH - SAMEENA BEGUM; NIRANJAN PANDA; CH. PRAVEENA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study presents the design and development of Enzalutamide (EZ)-encapsulated polycaprolactone (PCL) nanoparticles (NPs) for targeted prostate cancer therapy, employing a statistical Box–Behnken design to optimize formulation parameters. Methods: NPs were prepared through the emulsion solvent evaporation method and evaluated for particle size, entrapment efficiency (EE) %, and zeta potential. In vivo pharmacokinetic and cytotoxicity studies were carried out to ensure the in vivo efficacy of the optimised formulation. Results: The formulations exhibited particle sizes ranging from 148 nm to 219 nm, EE% between 70% and 92%, and zeta potentials from −13.4 mV to −32.5 mV, indicating good colloidal stability. Transmission electron microscopy confirmed spherical morphology, while Fourier-transform infrared spectroscopy (FTIR) revealed no significant chemical interactions between EZ and PCL, confirming compatibility. Cytotoxicity studies demonstrated enhanced anticancer activity of the optimized NPs, with a lower half-maximal inhibitory concentration (14.27 μg/mL) value compared to pure EZ (22.24 μg/mL), suggesting improved cellular uptake and therapeutic efficacy. In the pharmacokinetic evaluation, EZ-loaded optimized NPs (Opt-EZ-PCL-NPs) exhibited a threefold enhancement in area under the curve (34.42 μg.h/mL) (p<0.05) relative to the pure EZ suspension formulation (11.30 μg.h/mL) (p<0.05), reflecting improved systemic bioavailability. Conclusion: These findings support the potential of PCL-based nanocarriers as an effective delivery system for EZ in PC treatment.